2022
DOI: 10.3390/ijms231810215
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Mini-Panel Sequencing of ctDNA Allows Tumor Monitoring in Complex Karyotype Sarcomas

Abstract: Soft tissue sarcomas (STS) are rare tumors of mesenchymal origin with high mortality. After curative resection, about one third of patients suffer from distant metastases. Tumor follow-up only covers a portion of recurrences and is associated with high cost and radiation burden. For metastasized STS, only limited inferences can be drawn from imaging data regarding therapy response. To date there are no established and evidence-based diagnostic biomarkers for STS due to their rarity and diversity. In a proof-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In the literature [24,58,59] and previous works by our group [28][29][30][31][32][33][34]45], ctDNA is described as a potential biomarker for the prediction of STS, its recurrence, and minimal residual disease PLOS ONE after resection. However, it has not been shown if ctDNA can be used as a biomarker for therapy response and how ctDNA correlates with vital tumor mass during NRT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature [24,58,59] and previous works by our group [28][29][30][31][32][33][34]45], ctDNA is described as a potential biomarker for the prediction of STS, its recurrence, and minimal residual disease PLOS ONE after resection. However, it has not been shown if ctDNA can be used as a biomarker for therapy response and how ctDNA correlates with vital tumor mass during NRT.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted sequencing of ctDNA improves STS detection independent of its anatomic localization and can be performed anytime during the course of treatment. Quantification of ctDNA in the peripheral circulation might even surpass common imaging modalities in its sensitivity and specificity to detect tumors or metastases [26][27][28]. In previous works, the Department of Plastic and Hand Surgery, Medical Center-University of Freiburg, Faculty of Medicine, Freiburg, Germany, has shown that liquid biopsy can be used to monitor tumor dynamics, predict minimal residual disease and detect genetic tumor heterogeneities [3,[28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation